Impacts of Low Self-control and Opportunity Structure on Cyberbullying Developmental Trajectories: Using a Latent Class Growth Analysis - Cho, Sujung (Crime & delinquency, 2021)
This study tested self-control and opportunities theories to examine cyberbullying developmental trajectories through the estimation of a latent class growth analysis. Data from a 6-year longitudinal study of middle- and high-school students from South Korea were analyzed to examine if there are unique growth trajectories for cyberbullying perpetration when accounting for low self-control and opportunity factors. Results suggest that there are three distinct subgroups: (1) a normative trajectory group, (2) an increasing and late-peak group, and (3) an early onset and decreasing group. Low self-control was found to be significantly associated with early onset/decreasing cyberbullying. Opportunity to utilize cyberspace was significantly related with increasing/late peak cyberbullying but did not significantly mediate the effect of low self-control on class membership.